2021
DOI: 10.20473/javest.v2.i1.2021.10-14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molasses Addition on Physical and Chemical Quality of Corn Plant Silage Given Fermented Mother Liquor

Abstract: Background: Making silage added with additives can improve the quality of silage nutrition and speed up the fermentation process. Molasses are widely used by farmers as additives for making silage. The use of molasses can be replaced with Fermented Mother Liquor (FML) in making silage. Purpose: to determine the effect of molasses addition on physical and chemical quality of corn plant silage given Fermented Mother Liquor (FML). Method: Observative data collection by making direct observations on making silage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…in the fermentation of high-fiber feed ingredients, results in a decrease in dry matter content and an increase in water content, where the respiration process of the ingredients continues, resulting in a breakdown of glucose into CO2, H2O, and heat [22]. The research results showed that the addition of various kinds of additives, namely Fermented Mother Liquor (FML) and molasses, was known to increase the water content in silage because the form of each additive was a liquid substance which could increase the water content, thereby reducing the dry matter (DM) content [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the fermentation of high-fiber feed ingredients, results in a decrease in dry matter content and an increase in water content, where the respiration process of the ingredients continues, resulting in a breakdown of glucose into CO2, H2O, and heat [22]. The research results showed that the addition of various kinds of additives, namely Fermented Mother Liquor (FML) and molasses, was known to increase the water content in silage because the form of each additive was a liquid substance which could increase the water content, thereby reducing the dry matter (DM) content [23].…”
Section: Resultsmentioning
confidence: 99%
“…The high ash content in all treatments was thought to be because molasses has a high mineral content, thus causing high ash content in the silage. The ash content in the proximate analysis only determines the level of Nitrogen-Free Extract Material (NFE) contained in the feed [23].…”
Section: Resultsmentioning
confidence: 99%